Advancing Adjuvants for Mycobacterium tuberculosis Therapeutics - Enriquez, Ana B.; Izzo, Angelo; Miller, Shannon M.; Stewart, Erica L.; Mahon, Robert N.; Frank, Daniel J.; Evans, Jay T.; Rengarajan, Jyothi; Triccas, James A. (Frontiers in Immunology, 2021)
This abstract is not publicly available due to funding stipulations. The full article will be available upon publication.